Salt and water balance after sweat loss: A study of Bikram yoga. Issue 22 (23rd November 2020) - Alrefai, Hasan; Mathis, Shannon L.; Hicks, Sarah M.; Pivovarova, Aleksandra I.; MacGregor, Gordon G.
Abstract: Bikram yoga is practiced in a room heated to 105°F with 40% humidity for 90 min. During the class a large volume of water and electrolytes are lost in the sweat, specifically, sodium is lost, the main cation of the extracellular fluid. There is little known about the volume of sweat and the amount of sodium lost in sweat during Bikram yoga or the optimum quantity of fluid required to replace these losses. The participants who took part in this small feasibility study were five females with a mean age of 47.4 ± 4.7 years and 2.6 ± 1.6 years of experience at Bikram yoga. The total body weight, water consumed, serum sodium concentration, serum osmolality, and serum aldosterone levels were all measured before and after a Bikram yoga practice. Sweat sodium chloride concentration and osmolality were measured at the end of the practice. The mean estimated sweat loss was 1.54 ± 0.65 L, while the amount of water consumed during Bikram yoga was 0.38 ± 0.22 L. Even though only 25% of the sweat loss was replenished with water intake during the Bikram yoga class, we did not observe a change in serum sodium levels or serum osmolality. The sweat contained 82 ± 16 mmol/L of sodium chloride for an estimated total of 6.8 ± 2.1 g of sodium chloride lost in the sweat. The serum aldosterone increased 3.5‐fold from before to after Bikram yoga. There was a decrease in the extracellular body fluid compartment of 9.7%. Sweat loss in Bikram yoga predominately produced a volume depletion rather than the dehydration of body fluids. The sweating‐stimulated rise in serum aldosterone levels will lead to increased sodium reabsorption from the kidney tubules and restore the extracellular fluid volume over the next 24 hr. Abstract : A large amount of water and salt is lost in sweat during 90 min of Bikram yoga. This fluid loss produced a volume depletion of the extracellular fluid compartment rather than dehydration or disturbance in the body electrolyte levels. The lost fluid will be restored with salt in the diet over the next 24 hr.